Empirical study on the relationship between income smoothing and shareholders wealth among Malaysian listed companies / Ruslaina Haji Yusoff - Yusoff, Ruslaina (2001)
This research was carried out to identify the income smoothing and non-smoothing companies listed in the KLSE first board using Eckel's Index (1981) and to examine the relationship between the income smoothing and shareholder wealth (companies' share price). 298 listed companies have been selected as samples in the current study. Income before extraordinary items (El), pretax income (PI) and net income (NI) are used as an income measurement in Eckel's Index. Based on descriptive statistic, it was found that there are more smoothing than non-smoothing companies, based on all three income measurement. Based on t-test and Wilcoxon sign-rank test, the results indicated that there is no significant difference between cumulative abnormal return for smoothing and nonsmoothing companies at any income measurement (El, PI and NI). Furthermore, when size (measured by market equity) is examined between smoothing and non-smoothing companies, it was found that income smoothing does not depend on the size of the company. Further test indicates that there is no significant difference between cumulative abnormal return of large and small companies. Based on the results obtained from ANOVA, it showed that there is no significant difference of cumulative abnormal return between groups when income before extraordinary items and pretax income was used as income measurement in detecting the presence of income smoothing. However, there was a difference in cumulative abnormal return between industries when net income was being used as an income measurement. The univariate regression confirms the earlier result that there is no significant relationship between cumulative abnormal returns, income smoothing, firm size and industry. Thus, the result in the current study provides evidence that there is more smoothing than non-smoothing companies. However, investors in Malaysia during the study period (1994 - 1999) seem to ignore the smooth income streams. Thus, improvement in shareholders wealth is not the motivation for smoothing in Malaysia.